National Dam Inspection Program. Greenbrier State Park Dam & Dike (NDI Number-MD-00042) Potomac River Basin, Little Beaver Creek, Washington County, Maryland. Phase I Inspection Report. - CORPS OF ENGINEERS BALTIMORE MD BALTIMORE DISTRICT (1979)
The Greenbrier State Park Dam consists of an earth fill embankment approximately 64 feet high and 445 feet long. The principal spillway has a crest elevation of 151.5 feet or 8.1 feet below the top of the dam which is at an elevation 159.6. The principal spillway is a two stage rectangular reinforced concrete intake structure which connects to a 36 inch concrete water pipe that exits at elevation 97.0 into a stilling basin. A drawdown system that ties into the bottom of the rectangular intake at elevation 101.0 extends under the reservoir 149 feet to a perforated 36 inch B.C.C.M.P. 12 feet high. At the northeast side of the lake, an earthen dike 560 feet long and 10 feet high was constructed to retain flood pools. The 145 foot wide emergency spillway is located on the right abutment of the dike at an elevation of 153.5. Based upon the evaluation of the conditions as they existed on the date of the inspection and as revealed by visual observations, the condition of Greenbrier State Park Dam and Dike is assessed to be good. The spillway capacity, based upon the designed geometry, is assessed to be adequate because it safely passes full Probable Maximum Flood. However, additional hydraulic studies are warranted based upon the existing use of the emergency spillway as an access roadway and boat launching facility. Original contains color plates: All DTIC and NTIS reproductions will be in black and white.